2018
DOI: 10.1016/j.amjcard.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aortic Stiffness on Aortic-Root Growth Rate and Outcome in Patients With the Marfan Syndrome

Abstract: The Pediatric Heart Network randomized trial of atenolol versus losartan in the Marfan syndrome showed no treatment differences in the rates of aortic-root growth or clinical outcomes. In this report we present treatment effects on aortic stiffness and determine whether baseline aortic stiffness predicts aortic-root growth and clinical outcomes. Echocardiograms at 0, 6, 12, 24, and 36 months from 608 subjects (6 months to 25 years) who met original Ghent criteria and had a maximum aortic-root z-score (ARz) >3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…82 Therefore, it is surprising that a recent follow-up study of the largest clinical trial assessing losartan versus atenolol in patients with MFS found that treatment with atenolol >3 years decreased baseline aortic root stiffness, whereas losartan did not. 29,83 This study also found that patients with MFS with higher baseline stiffness measurements had the fastest rate of growth of the aortic root. Although these results favor the use of β-blockers over Atr1 inhibition to prevent aortic growth in patients with MFS, it remains unclear why an Atr1 blocker failed to block aortic stiffness.…”
Section: Closing Remarks and Future Perspectivessupporting
confidence: 55%
“…82 Therefore, it is surprising that a recent follow-up study of the largest clinical trial assessing losartan versus atenolol in patients with MFS found that treatment with atenolol >3 years decreased baseline aortic root stiffness, whereas losartan did not. 29,83 This study also found that patients with MFS with higher baseline stiffness measurements had the fastest rate of growth of the aortic root. Although these results favor the use of β-blockers over Atr1 inhibition to prevent aortic growth in patients with MFS, it remains unclear why an Atr1 blocker failed to block aortic stiffness.…”
Section: Closing Remarks and Future Perspectivessupporting
confidence: 55%
“…Perhaps unintuitively, increased stiffness (resistance to deformation) can associate with decreased vessel strength (ability to withstand stress without breaking), with one study measuring an approximately 30% decrease in vessel strength accompanied by a 72% increase in stiffness in aneurysmal versus nonaneurysmal ascending aorta [374,375]. Correlations between increased stiffness and aortic dilatation have been reported in numerous studies of both patients and mouse models of TAA [376][377][378][379][380][381][382][383][384][385][386][387][388][389][390].…”
Section: Adaptive and Maladaptive Roles Of "Aortic Stiffness"mentioning
confidence: 99%
“…In MFS patients, endothelial dysfunction and increased aortic stiffness are associated with aortic aneurysmal formation [ 48 , 49 , 50 ], and losartan attenuates impairment of endothelial function in MFS mice and patients ( Figure 3 ). Sellers et al reported that Fbn1 C1039G/+ mice crossed with hypotensive Agt1ar knockout mice ( Fbn1 C1039G/+ : Agt1ar −/− ) showed unabated aortic aneurysmal formation [ 51 ].…”
Section: Marfan Syndromementioning
confidence: 99%